2020
DOI: 10.18231/j.ijceo.2020.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of intraocular pressure measured by non-contact, rebound and goldmann applanation tonometer and their correlation with corneal thickness and true IOP in a general population

Abstract: To compare the Intraocular Pressure (IOP) measured by Non-contact tonometer (NCT), Rebound tonometer (RBT) and Goldmann Applanation tonometer (GAT) and their correlation with central corneal thickness (CCT) and true IOP. Reliability of each tonometer. Materials and Methods: 500 random patients aged 18 years and above were taken up for the study. Patients with anterior and posterior segment pathologies like corneal ulcer, leukoma, staphyloma, corneal lacerations, ectatic corneal conditions, corneal dystrophies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
(50 reference statements)
0
1
0
Order By: Relevance
“… 13 Regarding thickness, a study showed that NCT values were higher than GAT values in thin and normal corneas, but that IOP was overestimated in thicker corneas. 14 …”
Section: Discussionmentioning
confidence: 99%
“… 13 Regarding thickness, a study showed that NCT values were higher than GAT values in thin and normal corneas, but that IOP was overestimated in thicker corneas. 14 …”
Section: Discussionmentioning
confidence: 99%